Scrubbed Palm Fatty Acid Distillate as Vitamin E Concentrate - Amnart Soontornchatchawate; Supachai Chintanalert; Prakob Kitchaiya; Apinan Namkanisorn (Journal of Oleo Science, 2021)
Vitamin E (VitE) production from crude palm oil (CPO) has been extensively studied and industrially conducted. VitE in CPO is in the range of 600 to 1,000 ppm, and is usually produced from one of the main by-products of edible palm oil production, namely palm fatty acid distillate (PFAD). PFAD contains 4,000 to 5,500 ppm of VitE, and is produced from deodorization process of palm oil purification. This paper presents an innovative process of VitE concentrate production from CPO. A scrubber was designed and installed between the deodorizer and conventional PFAD scrubber. The main objective of this new scrubber was a recovery of glycerides from PFAD. This new scrubber is operated at 150 to 160℃. The scrubbed oil is named as Scrubbed Palm Fatty Acid Distillate (S-PFAD). This simple and efficient modified process can retrieve glycerides as S-PFAD at 0.3% recovery and it enhances VitE concentration in S-PFAD to the range of 28,000 to 32,000 ppm, which is the highest concentration of VitE that has ever been produced in the palm oil production. Fatty acids and glycerides in S-PFAD were esterified and transesterified to methyl esters. The methyl esters were evaporated from S-PFAD, and S-PFAD residue oil contained 24.7% VitE.
Keywords: Petroleum Processing and Analysis; Food Chemistry and Fat Analysis; Enhanced Oil Recovery Techniques